2019
DOI: 10.3389/fmicb.2019.01145
|View full text |Cite
|
Sign up to set email alerts
|

Bacteroides thetaiotaomicron Starch Utilization Promotes Quercetin Degradation and Butyrate Production by Eubacterium ramulus

Abstract: Consumption of flavonoids has been associated with protection against cardiovascular and neurodegenerative diseases. Most dietary flavonoids are subjected to bacterial transformations in the gut where they are converted into biologically active metabolites that are more bioavailable and have distinct effects relative to the parent compounds. While some of the pathways involved in the breakdown of flavonoids are emerging, little it is known about the impact of carbon source availability and community dynamics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 44 publications
0
35
0
1
Order By: Relevance
“…Our proteomic data showed altered proteins involved in acetate production and starch degrading associated with Bacteroides thetaiotaomicron and Parabacteroides distasonis , a commensal member of the gut microbiota, supporting bacteria functional changes. As such B. thetaiotaomicron can degrade starches and produce butyrate 62 . Although Bacteroides can have beneficial effects in health, 63 it has been reported that interaction between B. thetaiotaomicron and the enteric pathogens can enhance virulence and infection progression 64,65 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our proteomic data showed altered proteins involved in acetate production and starch degrading associated with Bacteroides thetaiotaomicron and Parabacteroides distasonis , a commensal member of the gut microbiota, supporting bacteria functional changes. As such B. thetaiotaomicron can degrade starches and produce butyrate 62 . Although Bacteroides can have beneficial effects in health, 63 it has been reported that interaction between B. thetaiotaomicron and the enteric pathogens can enhance virulence and infection progression 64,65 .…”
Section: Discussionmentioning
confidence: 99%
“…As such B. thetaiotaomicron can degrade starches and produce butyrate. 62 Although Bacteroides can have beneficial effects in health, 63 it has been reported that interaction between B. thetaiotaomicron and the enteric pathogens can enhance virulence and infection progression. 64,65 Furthermore, HAMSA feeding increased the proportion of an unknown Alphaproteobacteria in the faecal microbiota, similar to what has been observed in pigs fed a resistant starch diet.…”
Section: Discussionmentioning
confidence: 99%
“…Human fecal samples were used for in vitro incubations with quercetin. Samples from 9 subjects kept in frozen straws were aliquoted (~50 mg) on dry ice, weighted, and resuspended at 0.5 mg ml -1 final concentration with heavy vortexing in anaerobic 7N minimal medium supplemented with 20 mM sodium acetate (filter-sterilized through a 0.22-m pore diameter) [ 19 ]. Quercetin dihydrate, 97% w/w (Alfa Aesar) concentration was 0.125 mg ml -1 (0.4 mM) in the corresponding medium.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were processed as previously described [ 19 ]. Briefly, 200 μl samples were mixed with 1000 μl HPLC-grade methanol plus 20 μM genistein as internal standard, the suspension was bead beaten (2 min), heated (56°C for 20 min) and spun (10 min at 18, 000 g ).…”
Section: Methodsmentioning
confidence: 99%
“…The primary HMOS degraders could drive the microbial community in the infant gut via cross-feeding. As such, the intermediate breakdown products by one bacterial species serve as the substrate to support the growth of other microbes in the environment, resulting in indirect benefits for all species involved [ 11 , 12 , 13 , 14 ]. For instance, Bifidobacterium spp.…”
Section: Introductionmentioning
confidence: 99%